Papuan Volleyball Athlete's Physical Movement Literacy Performance - Qomarrullah, Rif'iy; Guntoro, Tri Setyo; Mujadi, Mujadi; Suratni, Suratni (Universitas Negeri Semarang, 2023)
The background of this research is the unknown level of physical condition of the volleyball athletes for the Papua team. This study aims to find out how good the physical condition level of the Papua volleyball athletes will be as candidates for the Papuan team. This research is a quantitative descriptive research, the data collection technique used is using a physical test. The sample in this study were young elite volleyball athletes. The data analysis technique used is descriptive statistics in the form of percentages. Based on the data on the overall results of tests on the physical condition of volleyball athletes from 37 male respondents, there were 7 people (19.44%) in the very good classification, 9 people good (25.82%), 10 people in the sufficient category (29.10). %), the unfavorable category is 5 people (12.89%), and 5 people are included in the very unfavorable category (12.89%). This physical condition can describe the actual physical condition of volleyball athletes who will be candidates for the Papuan team. These results describe several components that can influence it, including: speed, flexibility, strength, explosive power, agility, and endurance. Therefore, if there is research related to this study, it is advisable to update the applied method of instrument application as needed in the field.